2018
DOI: 10.4067/s0718-95162018005002201
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of a new bio-organic remediation as a bio-fungicide in fusarium-infested soils of watermelon monoculture areas from China

Abstract: Sustainably managed soils can increase soil quality, biodiversity, and reduce soil erosion and nutrient losses. In several regions of China, long-term monocultures such as watermelon are leading to severe degradation of soil biological functions due to contamination by dominant and deleterious microbes, particularly Fusarium spp., resulting in decreased soil productivity and quality.The main goal of this study was to assess a new bio-organic fertilizer in monoculture areas by testing the interactions between F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Remediation of Fusarium disease of long-term watermelon monoculture field soil using bio-organic material was also reported in China. This treatment significantly reduced the population pathogenic F. oxysporum and enhanced total beneficial bacteria in treated soils (Liu et al, 2018). The complex role of rhizhosphere microbal communities in plant health is well known, especially with regard to abundance and diversity (Fu et al, 2019).…”
Section: Effects Of Treatments On Disease Developmentmentioning
confidence: 96%
“…Remediation of Fusarium disease of long-term watermelon monoculture field soil using bio-organic material was also reported in China. This treatment significantly reduced the population pathogenic F. oxysporum and enhanced total beneficial bacteria in treated soils (Liu et al, 2018). The complex role of rhizhosphere microbal communities in plant health is well known, especially with regard to abundance and diversity (Fu et al, 2019).…”
Section: Effects Of Treatments On Disease Developmentmentioning
confidence: 96%
“…Multiple reviews have focused on the importance of soil microbial interactions, both with each other and with plants, and associated ecosystem functions to sustainable and high-quality food production. [198][199][200][201] Empirical studies have shown that soil microbial community composition and functioning are important drivers of ecosystem processes that promote plant growth and fitness such as nutrient cycling are critical for long-term sustainable plant production. 202,203 Effectively managing soil microbial communities for increased long-term sustainability and ecosystem resilience will be critical to ensure secure food systems and maintain or improve human health and well-being under future global change conditions.…”
Section: Soil Microorganisms and Human Health Current Statusmentioning
confidence: 99%
“…(3) Suppressing soil-borne diseases such as fusarium wilt in banana (Shen et al, 2014; HASSAN EL-RAMADY et al Zhang et al, 2014), pepper (Wu et al, 2015), cucumber (Huang et al, 2017), watermelon (Liu et al, 2018;Zhao et al, 2018;Xue et al, 2019), and generally acting as a biological control (Ma et al, 2018).…”
Section: The Bio-organic Fertilizers Derived From Alfalfamentioning
confidence: 99%